Surgical outcome after neoadjuvant chemotherapy and bevacizumab: results from the GeparQuinto study (GBG 44) - Gerber, Bernd; Von Minckwitz, Gunter; Eidtmann, Holger; Rezai, Mahdi; Fasching, Peter; Tesch, Hans; Eggemann, Holm; Schrader, Iris; Kittel, Kornelia; Hanusch, Claus; Solbach, Christine; Jackisch, Christian; et al. (Annals of Surgical Oncology, 2014)
Bevacizumab, a humanized monoclonal antibody against vascular endothelial growth factor, has shown increased pathological complete response rates when added to neoadjuvant chemotherapy. In various cancer types, bevacizumab treatment was accompanied by an increased risk of bleedings and other surgical complications. We assessed associated surgical complications.In the GeparQuinto trial, 1,948 patients were randomized to receive four cycles epirubicin/cyclophosphamide (EC, 90/600 mg/m(2) q3w) followed by four cycles docetaxel (D, 100 mg/m(2) q3w) each with (ECB-DB) or without (EC-D) bevacizumab (B, 15 mg/kg q3w) concurrent with chemotherapy. Surgery had to be performed not earlier than 28 days after the last bevacizumab infusion, but within days 21 and 35 after the last chemotherapy.In 743 (38.1 %) patients, a surgical complication (bleedings, hematomas, necrosis, wound infections, abscess) was documented prospectively. Baseline characteristics of the patients were well balanced between both arms. The breast-conserving surgery (BCS) rate (N = 502) was 69.1 % (EC-D) and 71.9 % (ECB-DB; p = 0.464). The first surgical procedure was performed at a median of 29 (EC-D) and 34 days (ECB-DB) after last chemotherapy with or without bevacizumab infusion (p < 0.001). Surgical complications were documented in 38 (10.9 %; EC-D) and 59 (15.0 %; ECB-DB) patients (p = 0.103). Surgical complications were significantly higher after ECD-DB only in patients treated with BCS (N = 53; p = 0.029) or in those requiring repeat surgery in order achieve clear margins (N = 23; p = 0.037) compared to the EC-D group.Addition of bevacizumab to neoadjuvant chemotherapy might be associated with an increased risk for surgical complications in patients treated with BCS or after repeated surgeries.
EVALuna2:17510